Naturaleza and citizenship in Modern Spain : From subject representation to the dawn of contemporary citizenship (17th-19th centuries) - Salvatto, Fabricio Gabriel (Almanack.)
The Constitution of Cadiz of 1812 defines the profiles of the spanish subject and spanish citizen, to ones a clearly modern citizen, to others, a still immersed subject in the corporate world of the Ancient Regime. Is still debated, therefore, if the gaditana constitution has the aspects of the modern citizenship or if it drags the conditions of the former local nature which tends to become universal in the Hispanic Empire. From the proposed Great Memorial of the Conde-Duque de Olivares and the Nueva Planta decrees of Felipe V, We intend to review the main questions which appears crystallized in the Novísima Recopilación, then discussed in the Cortes doceañistas. There the terms nature and citizenship played a central role in the discussions, as well as later uses of corporate conceptions.